(untitled) (Bangladesh Journal of Otorhinolaryngology, 2020)
Neuroendocrine carcinoma is an uncommon tumor. Primary NEC of the paranasal sinuses is extremely rare; only about 76 cases have been reported in literature. Unfortunately due to the rarity of this neoplasm, there are no specific recommendations regarding management of the disease. While Surgery was used in the past, chemoradiation now seems to be evolving as the treatment of choice. The clinical presentation, imaging studies, histopathological diagnosis with immunohistochemistry correlation, management protocols, and a brief review of literature of this rare tumor is discussed. Bangladesh J Otorhinolaryngol; April 2017; 23(1): 96-100